(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Artificial intelligence (AI) systems can – as stressed in a recent Council of Europe document – help safeguard regional and minority languages. This paper reflects on the potential of AI to address situations of linguistic marginalization and vulnerability, identifying the interdisciplinary collaboration as a necessary condition to push the discussion beyond the, certainly relevant, issues of translation and “access”, and towards the bi-directional relationship between AI and more complex and severe forms of epistemic injustice.